766 Rapid Trio-Exome sequencing for children on the paediatric critical care unit-the gift that keeps on giving. (17th August 2022) - Johnson, Suzannah; Alukrar, Shrirang; Bird, David; Eason, Jaqueline; Butland, Laura
Abstract : Aims: Monogenic paediatric onset disorders are rare and difficult to diagnose but may be more common within Paediatric Critical Care patients. Rapid Trio Exome Sequencing has been available for patients since October 2019. This service is rapidly evolving and we have seen a number of new diagnoses with repeated tests or in the light of changing clinical features. We aimed to analyse referrals and outcomes for Rapid Trio Exome Sequencing in our Paediatric Critical Care to identify trends and diagnostic yield. Methods: A retrospective review of case notes and outcomes in Paediatric Critical Care referrals for Rapid Trio Exome Sequencing in Nottingham PCCU from October 2019 - 1st December 2021 was carried out. Results: A total of 21 referrals were made from PCCU to the Nottingham Clinical Genetics Team. A diagnosis was found in 7/21 (33%), a variant of uncertain significance in 1/21 (4%) and one case was on-going. Of those with a diagnosis: 3/7 had de novo mutations, 3/7 were recessive inheritance disorders and 1/7 had X-linked inheritance. In all 7 cases where an overarching diagnosis was made there was a significant impact on subsequent management. Conclusion: Rapid Trio Exome sequencing is a powerful diagnostic tool which has allowed accurate diagnosis of 7 complex paediatric critical care cases where no cause was identified in previous genetic testing. This has subsequently impacted acute clinical management and specialist/genetic follow up. We recommend Trio Exome Sequencing in the light of new clinical features even if historical testing has been negative.